The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1111/j.1469-8749.2012.04258.x
|View full text |Cite
|
Sign up to set email alerts
|

Motor function after selective dorsal rhizotomy: a 10‐year practice‐based follow‐up study

Abstract: Aim  The aim of this study was to explore changes in motor function up to 10 years after selective dorsal rhizotomy (SDR). Method  The participants comprised 29 children (20 males, nine females) with bilateral spastic diplegia who were consecutively operated on at a median age of 4 years and 3 months and followed until a median age of 15 years. SDR was combined with physiotherapy and regular follow‐up visits. The distribution of preoperative Gross Motor Function Classification System (GMFCS) levels was as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
67
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 29 publications
(58 reference statements)
4
67
0
5
Order By: Relevance
“…However, function (as measured with GMFM-88) seemed to improve sharply for up to 3 years after SDR but, thereafter, a significant reduction was witnessed. In a recent study the authors [9] showed that even 10 years after the operation, SDR, combined with physiotherapy in children with bilateral spastic diplegia, resulted in reduced muscle tone in the majority of patients assessed (n=29) and the mean increase in GMFM-66 was 10.6. The procedure led not only to reduced spasticity but also to improved gait for a decade after the operation [10].…”
Section: Discussionmentioning
confidence: 98%
“…However, function (as measured with GMFM-88) seemed to improve sharply for up to 3 years after SDR but, thereafter, a significant reduction was witnessed. In a recent study the authors [9] showed that even 10 years after the operation, SDR, combined with physiotherapy in children with bilateral spastic diplegia, resulted in reduced muscle tone in the majority of patients assessed (n=29) and the mean increase in GMFM-66 was 10.6. The procedure led not only to reduced spasticity but also to improved gait for a decade after the operation [10].…”
Section: Discussionmentioning
confidence: 98%
“…The study by van Wely et al 1 is innovative in examining the effect of personal and environmental factors on physical activity. In their study, children with cerebral palsy who walk took fewer steps per day on weekends and fewer steps per day than recommendations for children without physical impairments.…”
mentioning
confidence: 99%
“…Although van Wely et al 1 measured steps walked per day as an indicator of physical activity, their recommendation to increase physical activity on weekends is not specific to walking. A number of considerations underlie the question of whether a child with cerebral palsy should be encouraged to increase physical activity by walking more often or for longer periods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2 3 A recent prospective study also did not show improved scores in the Gross Motor Function Classification System (GMFCS) during 10 years of follow-up. 4 However, we knew of reports of children with spasticity experiencing sustained improvement in motor function after the procedure. These data suggested that children whose walking was primarily impaired by spasticity rather than weakness, contractures, or poor muscle control could benefit.…”
mentioning
confidence: 99%